2012
DOI: 10.1007/s11356-012-0772-9
|View full text |Cite
|
Sign up to set email alerts
|

Reference gene selection for qPCR in mussel, Mytilus edulis, during gametogenesis and exogenous estrogen exposure

Abstract: We demonstrate that the experimental results are highly dependent on the reference gene chosen and that statistically significant contrasting differences between sample groups are present or absent depending on the reference gene employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 21 publications
3
29
0
Order By: Relevance
“…Some studies have been recently published to find the best reference genes for qPCR analysis in bivalves (Araya et al 2008;Dheilly et al 2011;Cubero-Leon et al 2012;Mauriz et al 2012;Siah et al 2012;Du et al 2013) and showed that for each species, tissue, challenge and even reproductive state the optimal reference gene may change. Although it is known that the selection of an inappropriate reference gene could alter the results, no routine analysis to find the most stable gene are usually made (Bustin et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have been recently published to find the best reference genes for qPCR analysis in bivalves (Araya et al 2008;Dheilly et al 2011;Cubero-Leon et al 2012;Mauriz et al 2012;Siah et al 2012;Du et al 2013) and showed that for each species, tissue, challenge and even reproductive state the optimal reference gene may change. Although it is known that the selection of an inappropriate reference gene could alter the results, no routine analysis to find the most stable gene are usually made (Bustin et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Living Resour. 27, 147-152 (2014) but in mollusks (Martínez-Fernández et al 2010) and also in bivalves (Araya et al 2008;Cubero-Leon et al 2012;Dheilly et al 2011;Du et al 2013;Mauriz et al 2012;Siah et al 2012); because different species in different circumstances are able to modify their transcriptome to overcome the situation.…”
Section: Introductionmentioning
confidence: 99%
“…Assembled sequence which could be annotated as the same protein again with best hit was used for candidate reference gene searching. Finally, a total of 12 commonly used candidate reference genes [18,35,44-47], including ACT , GAPDH , Cytochrome C (CC), Cytochrome B (CB), elongation factor 1-β ( EF-1-β ), Ubiquitin ( UBQ ), TATA-box binding protein (TBP), 60S ribosomal protein L16 ( RPL16 ), DEAD-box RNA helicase ( HELI ), β-Tubulin ( TUB ), Cyclophilin A ( CYP ), and Histone H3.3 ( His3.3 ) were selected for expression stability analysis (Table 1). …”
Section: Methodsmentioning
confidence: 99%
“…For example, in scallops, the most frequently used reference gene in qRT-PCR is ACT , but without evaluation. By far, in the limited studies on reference gene selection for bivalve species, most of them focused on single tissues, such as haemocyte in parasite attacked flat oyster ( Ostrea edulis ) [18] and bacteria infected soft-shell clam ( Mya Arenaria ) [17], and gonad in mussel ( Mytilus edulis ) [35] and lion’s paw scallop ( Nodipectensubnodosus ) [36]. Although the expression stability of candidate reference genes was assessed in several tissues of Yesso scallop ( Patinopecten yessoensis ) with respect to starvation treatment, the reference genes were recommended for different single tissues, and those could be generally used among tissues were not evaluated or identified [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation